High-thermal-conductivity super-strong electromagnetic shielding composite phase change material based on MXene-based aerogel

Through the composite phase change material based on MXene-based aerogel, the MXene@CS three-dimensional frame is formed using directional freezing and vacuum impregnation technology, and the PEG phase change material is adsorbed, which solves the problems of low thermal conductivity and insufficient electromagnetic shielding performance of composite phase change materials, and achieves multifunctional performance of high thermal conductivity, super-strong electromagnetic shielding and photothermal conversion.

CN119799281APending Publication Date: 2025-04-11ZHONGBEI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510011540.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Composite phase change materials are difficult to stably exert thermal management and electromagnetic shielding performance, and their thermal conductivity is not high.

Method used

A high thermal conductivity and super electromagnetic shielding composite phase change material based on MXene-based aerogel is used to form a three-dimensional frame material through directional freezing and vacuum impregnation technology, and a high load PEG phase change material is adsorbed thereon.

Benefits of technology

It realizes the high thermal conductivity of composite phase change materials (up to 1.433W/(m·K) and super electromagnetic shielding performance (up to 40dB in the X-band), and also has the photothermal/electrical conversion function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799281A_ABST
    Figure CN119799281A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity super-strong electromagnetic shielding composite phase-change material based on MXene-based aerogel, a three-dimensional frame structure is built by adopting a mode that MXene nanosheets are directionally arranged on a chitosan skeleton, a phase-change material PEG is adsorbed to form the composite phase-change material, the highest latent heat value of 174.86 J / g is achieved, the heat conductivity coefficient is also increased to 1.446 W / (m.K), and the composite phase-change material has the advantages of high thermal conductivity, high electromagnetic shielding performance and the like. The electromagnetic shielding performance can reach 40dB, and the material also has good electrothermal conversion performance and photo-thermal conversion performance, and has a good application prospect in the field of battery thermal management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite phase change materials, and relates to a composite phase change material with excellent thermal conductivity, electromagnetic interference shielding, and electrothermal and photothermal conversion energy storage performance, and in particular to a composite phase change material based on a MXene-based aerogel framework structure and a preparation method thereof. Background Art

[0002] As society continues to develop, traditional oil and coal resources are rapidly consumed, and the use of other emerging energy sources has become a hot topic. Electricity, as a clean energy, has become a major energy source for energy conversion and is widely used. Phase change materials, as excellent materials for energy conversion, can achieve most forms of energy conversion processes through modification and are favored by researchers. Among them, polyethylene glycol (PEG), as an organic phase change material, has been widely studied due to its advantages such as high energy storage density and adjustable phase change temperature.

[0003] However, due to the leakage problem that phase change materials are prone to during the phase change process, as well as the low electrical insulation and thermal conductivity of the materials, their application scenarios are limited. Therefore, the key to studying composite phase change materials is to prepare composite phase change materials with good shape stability and modify them to improve their thermal and electrical conductivity.

[0004] In order to solve the leakage problem of traditional phase change materials during application and improve their thermal conductivity, researchers have prepared composite phase change materials to achieve structural shaping and performance improvement. In addition, the electrical and thermal conductivity of phase change materials can be improved by adding conductive and thermal conductive materials such as carbon nanotubes (CNTs) and expanded graphite (EG).

[0005] Sun Qinrong (Research on energy storage characteristics and application of composite phase change materials with electrothermal conversion function [D]. Southwest Jiaotong University, 2020.) Using PEG as phase change material, CNTs as thermal conductive skeleton material, and CaCl2 as ligand, 2+ By coordinating with the PEG terminal hydroxyl group, a new functional composite phase change material with high thermal conductivity was synthesized in one step using the coordination replacement method. Its thermal conductivity increases with the increase of CNTs content. When the CNTs content is 20wt%, the thermal conductivity is 0.91W / (m·K).

[0006] Xie et al. (MXene-modified bio-based pitaya peel foam / polyethylene glycol composite phase change material with excellent photo-thermal conversion efficiency, thermal energy storage capacity and thermal conductivity[J]. Journal of Energy Storage, 2024, 78: 110089.) used a simple vacuum impregnation method to encapsulate polyethylene glycol (PEG) into MXene-modified pitaya peel-based porous carbon to prepare a new type of multifunctional phase change composite material. The MXene-modified bio-based pitaya peel foam / polyethylene glycol phase change composite material (PEG / BPC@M) exhibited a high loading ratio (95.4%) and a thermal conductivity of 0.566 W / (m·K).

[0007] Bai et al. (Directional chitosan / carbon fiber powder aerogel supported phase change composites for effective solar thermal energy conversion and hot compression[J]. Journal of Energy Storage, 2022, 56.) successfully prepared PA / CS@CFP phase change material by introducing CFP and using CS@CFP composite aerogel as the supporting matrix for vacuum impregnation. They can achieve high loading rate (>94%) and maintain good embedding ability, high enthalpy (211.9~257.5J / g), thermal stability, solar-thermal energy conversion and storage capacity.

[0008] Zhang et al. (Anisotropic cellulose nanofiber / chitosan aerogel with thermal management and oil absorption properties[J]. Carbohydrate polymers, 2021,264: 118033.) freeze-dried chitosan (CS) into aerogel and found that the skeleton was weak and the mechanical strength was insufficient, resulting in serious leakage of the adsorbed phase change material.

[0009] It can be seen that the performance of the above-mentioned phase change composite materials is not outstanding due to the serious stacking tendency of MXene nanosheets and the weak interconnection between adjacent nanosheets. Even though MXene in the form of three-dimensional aerogel can better adsorb phase change materials and encapsulate them in porous skeletons to prevent leakage during the phase change process, the intermolecular interaction force of the phase change material is weak due to the inability to form an interconnected structure, and heat is not easily transferred. Due to its short chain structure and dispersed arrangement, the thermal conductivity cannot be better improved, resulting in the thermal conductivity coefficients of the above-mentioned phase change composite materials not being too high.

[0010] At the same time, none of the above documents mentions the electromagnetic shielding performance of phase change composite materials. Phase change materials themselves do not have electromagnetic shielding performance. Even with the support of functional materials such as MXene, it is difficult to ensure the electromagnetic shielding performance of composite materials because it cannot form a regular arrangement in the aerogel structure. Summary of the invention

[0011] The purpose of the present invention is to solve the problem that composite phase change materials are difficult to stably exert thermal management and electromagnetic shielding performance, and to provide a high thermal conductivity and ultra-strong electromagnetic shielding composite phase change material based on MXene-based aerogel.

[0012] The high thermal conductivity and super electromagnetic shielding composite phase change material based on MXene-based aerogel described in the present invention uses MXene and chitosan as raw materials. The mixed solution is quickly and directionally frozen, and then vacuum dried to obtain an aerogel framework material, which is then carbonized at high temperature to obtain a MXene@CS three-dimensional framework material. The molten phase change material PEG is vacuum impregnated and adsorbed to obtain a shape-stable composite phase change material PEG@MC.

[0013] Specifically, the present invention is to put the mixed solution into a polytetrafluoroethylene mold with a copper plate at the bottom, and immerse it in liquid nitrogen for rapid directional freezing. The directional freezing is completed with the help of a specific mold, the entire mold is polytetrafluoroethylene, and only the bottom is set as a copper plate, so that the heat of the mixed solution can only be quickly exchanged with liquid nitrogen through the bottom copper plate in a directional manner, thereby forming an ice crystal structure from bottom to top.

[0014] The MXene in the present invention acts as a thermal conductor and a conductive filler at the same time. However, if MXene is directly subjected to ordinary freeze-drying, although the three-dimensional network structure of the aerogel skeleton can be guaranteed to a certain extent, the supporting force of the aerogel structure is very weak. Not only can the phase change material not be adsorbed, but serious stacking will also occur, affecting the basic performance of the aerogel.

[0015] Therefore, in order to give full play to the characteristics of MXene nanosheets and ensure their excellent mechanical properties, the present invention introduces chitosan, a polymer material containing a large number of surface oxygen-containing polar groups, which is assembled with MXene through hydrogen bond interactions to form a high-strength functional nanocomposite material.

[0016] In addition, during the process of liquid nitrogen freezing to form aerogel, if the ordinary direct quick freezing process is adopted, the temperature is not low enough to quickly and directly form ice crystals. Although the formed aerogel can adsorb phase change materials, the MXene therein is severely stacked and cannot be arranged regularly to form a three-dimensional interconnected structure.

[0017] Therefore, the present invention further adopts a directional freezing method, so that MXene can be firmly supported by CS while inducing it to be regularly arranged to form a continuous three-dimensional arrangement network, which can not only construct an aerogel structure with a high loading rate, but also have more properties such as thermal management and electromagnetic shielding.

[0018] Furthermore, in the aerogel framework material of the present invention, the mass ratio of MXene to chitosan is preferably 1:1 to 2.5.

[0019] Furthermore, the present invention preferably uses a MXene suspension with a concentration of 7 to 10 mg / mL and chitosan to form a mixed solution.

[0020] Furthermore, in the composite phase change material prepared by the MXene@CS three-dimensional framework material adsorbing the phase change material PEG, the loading amount of the phase change material can reach more than 98% of the total mass of the composite phase change material.

[0021] Furthermore, the present invention also provides a method for preparing the composite phase change material, which specifically comprises: 1) Prepare a MXene suspension with a concentration of 7-10 mg / mL; 2) preparing chitosan suspension and adjusting the pH value of the suspension to 5-6; 3) Mixing to obtain a mixed solution of MXene and chitosan, eliminating bubbles and placing it in a polytetrafluoroethylene mold on a copper bottom plate, rapidly freezing it in liquid nitrogen, and vacuum drying it in a freeze dryer to obtain an aerogel frame material; 4) Carbonizing the aerogel framework material at 380-400°C to obtain the MXene@CS three-dimensional framework material; 5) The MXene@CS three-dimensional framework material and excess PEG were placed in a vacuum oven at 80°C for vacuum impregnation treatment to obtain a PEG@MC composite phase change material.

[0022] Preferably, the present invention selects to use 1 wt % acetic acid solution to adjust the pH value of the chitosan suspension, and after the adjustment, a chitosan solution in which chitosan is fully dissolved can be obtained.

[0023] More preferably, the high temperature carbonization time for the aerogel frame material is 2 to 4 hours.

[0024] More preferably, the present invention is to vacuum immerse the MXene@CS three-dimensional framework material in excess molten PEG for 8 to 10 hours to fully absorb the molten PEG.

[0025] Based on the excellent conductivity of MXene and its potential advantages in the field of electromagnetic interference shielding due to its special layer structure, as well as the excellent light radiation absorption ability of MXene and carbonized CS, this invention has prepared a new type of aerogel three-dimensional skeleton, which is vacuum impregnated with composite PEG to achieve a loading of more than 98%. While ensuring a high loading rate, the thermal conductivity of the composite phase change material is increased by more than 3 times, reaching a maximum of 1.433W / (m·K). In addition, the composite phase change material also has excellent electromagnetic shielding performance, with a maximum of more than 40dB in the full range of the X-band (12-18GHz).

[0026] The composite phase change material of the present invention has excellent electromagnetic shielding and good thermal conductivity, and also has a certain photothermal / electrical heat conversion function, which is beneficial for some equipment with long-term charge and discharge cycle requirements, such as the heat flow of batteries. It not only prevents local overheating and even thermal runaway problems, but the photothermal conversion function can also enable the entire battery or battery pack to convert energy under sunlight to store heat, which can be further utilized for the operation of equipment under extremely cold conditions, and can be placed in the equipment casing as a thermal management module. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a synthesis flow chart of the composite phase change material of the present invention.

[0028] Figure 2 These are the SEM images and EDS spectra of three-dimensional framework materials and composite phase change materials.

[0029] Figure 3 It is the Fourier transform infrared spectrum of composite phase change materials and raw materials.

[0030] Figure 4 It is the XRD diagram of composite phase change material and raw materials.

[0031] Figure 5 This is the XPS energy spectrum of three-dimensional framework materials and composite phase change materials.

[0032] Figure 6 These are the DSC and TGA curves of different composite phase change materials.

[0033] Figure 7 It is a leakage rate test of different composite phase change materials.

[0034] Figure 8 These are the test results of thermal conductivity of different composite phase change materials.

[0035] Fig. 9 It is a graph of electromagnetic shielding performance of different composite phase change materials.

[0036] Fig.10 This is a test chart of the light-to-heat conversion capability of different composite phase change materials. Implementation

[0037] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0038] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0039] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0040] The high thermal conductivity and super electromagnetic shielding composite phase change material based on MXene-based aerogel of the present invention is specifically according to Figure 1 The process was prepared as shown in the flowchart.

[0041] First, a MXene solution was prepared using Ti3AlC2 MAX phase precursor as raw material: 2g LiF was added to 30mL of 12M HCl solution, stirred continuously for 30min, 2g Ti3AlC2 MAX phase precursor was added, stirred at 35°C for 24h, and the Al layer was etched away; deionized water was added to the solution after etching, centrifuged at 8000rpm for 10min, the supernatant was discarded, deionized water was continued to be added, and the above operation was repeated 6 to 7 times until the pH value of the supernatant was 6, and the washing was completed; the product was placed in low-temperature ethanol at 0 to 30°C, and ultrasonicated at 40kHz for 10min under an inert atmosphere, during which time ice bags or ice cubes were used to cool down, and the dark green supernatant containing layered MXene nanosheets was collected as the raw material of the MXene solution.

[0042] After preparing a suspension with a certain amount of chitosan and adjusting the pH value to 5-6, it is mixed with the MXene solution raw material and loaded into a polytetrafluoroethylene mold with a copper plate at the bottom. Liquid nitrogen is used for rapid direction freezing, and the aerogel framework material is obtained by vacuum drying in a freeze dryer. The MXene@CS three-dimensional framework material is obtained by carbonization at 400°C.

[0043] The PEG material was fully adsorbed in the MXene@CS three-dimensional framework material by vacuum impregnation method to prepare the PEG@MC composite phase change material.

[0044] The PEG@MC composite phase change material prepared by the present invention has a variety of excellent thermal management properties, including excellent thermal conductivity, super strong electromagnetic shielding effect and good light-to-heat conversion efficiency. Example

[0045] Example 1

[0046] Chitosan (CS) was added to water and stirred to form a 2.5 wt % chitosan suspension, and the pH value of the suspension was adjusted to 5-6 with 1 wt % acetic acid solution.

[0047] Take 4 mL of the chitosan suspension and mix it with 19.35 mL of 7.75 mg / mL MXene suspension to obtain a mixed solution with a mass ratio of MXene to chitosan of 1.5:1. After the mixed solution is fully stirred and bubbles are eliminated, it is placed in a polytetrafluoroethylene mold with a copper plate at the bottom, immersed in liquid nitrogen for rapid directional freezing, and then placed in a freeze dryer for vacuum drying for 72 hours to obtain an aerogel frame material.

[0048] The aerogel framework material was placed in a tubular furnace, heated to 400°C and carbonized for 2 hours to obtain a MXene@CS three-dimensional framework material, recorded as MC1.

[0049] MC1 and excess PEG were placed in a beaker and placed in a vacuum oven at 80°C for 8 hours to allow MC1 to fully absorb the molten PEG. After cooling, MC1 was taken out and the excess PEG on the surface was removed with filter paper to obtain a shape-stable PEG@MC composite phase change material, which was recorded as PEG@MC1.

[0050] Hitachi Regulus8100 and Sigma300 electron scanning microscopes were used to observe the surface micromorphology of the prepared MXene@CS three-dimensional framework materials and PEG@MC composite phase change materials, and the element content on the surface of the three-dimensional framework materials was tested. The results are as follows: Figure 2 shown.

[0051] from Figure 2From the SEM images of the MXene@CS three-dimensional framework materials at different magnifications in (a-d), it can be seen that the three-dimensional framework material formed by the chitosan support between the MXene nanosheets shows a highly porous longitudinal brick-like directional growth microstructure, and the presence of chitosan gives the three-dimensional framework material certain mechanical properties. This three-dimensional framework material exhibits a 3D interconnected porous structure caused by the formation of large ice crystals during the freezing process, with large pores over 50 μm wide, and the presence of a large number of voids provides a large number of sites for the attachment of PEG. Therefore, this three-dimensional porous structure formed by radial growth through directional freezing of the bottom copper plate has the ability to adsorb a large amount of PEG, and the directional growth structure ensures that the composite phase change material has a good three-dimensional thermal conductivity path when it is formed.

[0052] in addition, Figure 2 The EDS energy spectrum element mapping of the three-dimensional framework material shows that it is mainly composed of Ti and C elements.

[0053] Figure 2 In (e-k), SEM images of PEG@MC composite phase change materials at different magnifications are further given. In the figure, it can be observed that a large amount of PEG is adsorbed on the three-dimensional framework material, and a small number of unfilled small holes can be observed at a larger magnification. The vertical bright stripes on the composite phase change material are another microscopic manifestation of the oriented three-dimensional MXene structure. This regular vertical line is the edge formed by the longitudinal arrangement of the three-dimensional oriented structure. Even if it is filled with PEG, it can still be shown in the cross section. This structure enhances the mechanical strength of the PEG@MC composite phase change material during the phase change process, maintains the thermal shape stability and low leakage of PEG, and enhances the heat transfer performance of the composite phase change material.

[0054] In summary, the PEG@MC composite phase change material prepared in the present invention successfully constructs a three-dimensional thermal conductive framework, which not only has a high PEG adsorption capacity, but also its 3D interconnection pathway still exists after PEG adsorption.

[0055] Figure 3 The infrared spectra of the PEG@MC composite phase change material and the key materials in its preparation process are provided. The characteristic peaks of the composite phase change material are located at 2893cm -1 CH and 1108cm -1 The COC nearby is similar to the characteristic peak of PEG, which may be due to the fact that a large amount of PEG is firmly adsorbed inside MC under the action of capillary force and hydrogen bonding. -1 The tensile vibration of Ti-C is shown in the range of 3425cm -1 and 1360cm -1 The peak at 1108 cm is attributed to the stretching vibration of the OH single bond.-1 A small and broad absorption peak appeared at 2885 cm, which was mainly due to the stretching vibration of the COC single bond on chitosan. -1 and 2958cm -1 The two obvious characteristic absorption bands at are caused by CH of chitosan. The absorption peaks of NH in MXene and chitosan fluctuate, indicating that some hydrogen bonds may be formed between MXene and chitosan, proving that MXene and chitosan are successfully cross-linked and chitosan is successfully introduced into the MXene sheet.

[0056] Figure 4 By further testing the X-ray diffraction patterns of the PEG@MC composite phase change material and the key materials in its preparation process, its crystal structure was analyzed and the successful synthesis of the product was inferred.

[0057] In the figure, the MC characteristic peak at 2θ=6.6° comes from the (002) plane of MXene, and the two typical diffraction peaks of PEG at 2θ=19.3° and 23.5° correspond to its (120) and (130) crystal planes, respectively. There is no significant difference in the diffraction peaks of the PEG@MC composite phase change material after PEG and MXene are combined, and due to the low mass fraction of MXene in the composite phase change material, the characteristic peaks of MXene are difficult to detect.

[0058] Figure 5 The three-dimensional framework material and composite phase change material were further tested by X-ray energy spectrum using the American Thermo Scientific K-Alpha. The Al Kα source (Mono AlKα) XPS energy used was 1486.6 eV, and all XPS spectra were corrected by the C1s line of 284.8 eV.

[0059] from Figure 5 From the full spectrum analysis of (a), it can be seen that the element content of the three-dimensional framework material MC1 is dominated by C. This is because chitosan is used in the three-dimensional framework material and it is carbonized, and MXene can be regarded as a TiC composition, so the proportion of C element is relatively large. The disappearance of Al 2p proves that Al has been completely etched by HF, and the appearance of Cl 2p peak is attributed to the presence of HCl during the etching process; (a') Ti 2p shows the classic MXene TiC at 454.9eV, Ti(II) at 455.7eV, Ti(III) at 456.7eV, TiO2 at 458.6eV and their corresponding satellite peaks. The results of the oxidation peaks indicate that the degree of oxidation of the three-dimensional MXene framework is extremely low during the entire preparation process of the present invention; and (a'') C 1s shows the 284.8eV peak of CC, the 281.6eV peak of C-Ti, the 286.6eV peak of CO, and the 289.1eV peak of OC=O.

[0060] and Figure 5 In the XPS spectrum of the composite phase change material in (b), due to the large proportion of PEG in the composite material, its elements and chemical bonds are basically the same as those of pure PEG, mainly composed of two elements, C and O. The C 1s fitting curve in (b') shows the peaks of CC at 284.8eV and CO at 286.3eV. At the same time, C and O account for a large proportion, corresponding to the PEG structure.

[0061] In summary, a stable cross-linked structure was formed between chitosan and MXene through stable hydrogen bonding, and a large amount of PEG was successfully loaded on the formed aerogel skeleton.

[0062] Example 2

[0063] 4 mL of 2.5 wt% chitosan suspension was taken and mixed with 12.9 mL of 7.75 mg / mL MXene suspension so that the mass ratio of MXene to chitosan in the mixed solution was 1:1. A shape-stable composite phase change material was prepared according to the method in Example 1 and was recorded as PEG@MC2.

[0064] Example 3

[0065] 4 mL of 2.5 wt% chitosan suspension was taken and mixed with 6.45 mL of 7.75 mg / mL MXene suspension so that the mass ratio of MXene to chitosan in the mixed solution was 0.5:1. A shape-stable composite phase change material was prepared according to the method in Example 1 and was recorded as PEG@MC3.

[0066] Comparative Example 1

[0067] Take a certain amount of 7.75 mg / mL MXene suspension, stir it in a magnetic stirrer for 30 minutes to evenly disperse it and eliminate bubbles, then put it into a polytetrafluoroethylene mold with a copper plate at the bottom, immerse it in liquid nitrogen for rapid direction freezing, and put it in a freeze dryer for vacuum drying for 72 hours to obtain an aerogel framework material.

[0068] The aerogel framework material was placed in a tubular furnace, heated to 400°C and carbonized for 2 hours to obtain a MXene three-dimensional framework material.

[0069] The MXene three-dimensional framework material and excess PEG were placed in a beaker and placed in a vacuum oven at 80°C. An attempt was made to adsorb the molten PEG into the interior of the MXene three-dimensional framework material by vacuum impregnation. As a result, the MXene three-dimensional framework material collapsed directly and was unable to adsorb the molten PEG to obtain a phase change composite material.

[0070] This is because the pure MXene three-dimensional framework material has very weak supporting force. Not only can it not adsorb molten PEG in a vacuum environment, but it will also cause serious stacking due to the vacuum conditions, affecting its basic performance.

[0071] Comparative Example 2

[0072] A certain amount of the chitosan suspension prepared in Example 1 was taken, stirred in a magnetic stirrer for 30 min to uniformly disperse and eliminate bubbles, then loaded into a polytetrafluoroethylene mold with a copper plate at the bottom, immersed in liquid nitrogen for rapid directional freezing, and placed in a freeze dryer for vacuum drying for 72 h to obtain a CS skeleton material.

[0073] The pore size of the obtained CS skeleton material is too large and unevenly distributed. When the CS skeleton material is placed in molten PEG, the molten PEG cannot be adsorbed and encapsulated in the skeleton.

[0074] Comparative Example 3

[0075] A mixed solution of MXene and chitosan in a mass ratio of 1.5:1 was prepared according to Example 1, and after being fully stirred and bubbles eliminated, it was loaded into a polytetrafluoroethylene mold without a copper plate at the bottom, immersed in liquid nitrogen for non-directional freezing, and then placed in a freeze dryer for vacuum drying for 48 hours to obtain an aerogel frame material.

[0076] Then, a composite phase change material was prepared according to the method of Example 1, and was recorded as PEG@MC4.

[0077] Application Example 1

[0078] The heat storage capacity and thermal stability of the composite phase change materials prepared in Examples 1 to 3 were tested and compared with those of pure PEG.

[0079] The DSC test uses a TA Q20 differential scanning calorimeter to increase the temperature from 30°C to 80°C at a rate of 3°C / min, and then cool it from 80°C to 30°C at a rate of 3°C / min to test the heat storage and release thermal management performance of the composite phase change material.

[0080] Figure 6 (a) is a comparison of DSC data of composite phase change material and PEG. The composite phase change material in the figure has a strong enthalpy value. PEG@MC3, which has the lowest enthalpy value among the three materials, also reaches 174.86 J / g. Further calculation shows that the enthalpy efficiency and relative enthalpy efficiency of the material reach 93.1% and 94.8%, respectively, which has a strong heat storage capacity.

[0081] The thermal properties of the composite phase change material were characterized by TGA test using a Netzsch STA 449 F3 tester. The test conditions were a nitrogen environment with a heating rate of 10°C / min from room temperature 30°C to 800°C.

[0082] Figure 6 (b) shows that the decomposition temperature of PEG is about 335-343℃, which is due to the decomposition of PEG molecular chains. The composite phase change material maintains the same trend as PEG before 350℃. After 350℃, with the support of the high thermal conductivity aerogel skeleton, the external heat can be quickly transferred to the interior of the phase change material, so that the PEG inside the composite phase change material reaches the thermal decomposition temperature earlier than pure PEG, so the composite phase change material decomposes faster than pure PEG; when it reaches about 400℃, the internal temperature of pure PEG also reaches the thermal decomposition temperature, so after 400℃, the thermal decomposition rates of the composite phase change material and PEG tend to be consistent; finally, PEG is basically completely decomposed after 430℃, and due to the existence of the skeleton, the composite phase change material no longer decomposes after 430℃, but the mass fraction does not reach 0%. At the same time, the TGA curve of the composite phase change material has only a very small amount of mass remaining at 800℃, which further illustrates the high loading rate of the composite phase change material.

[0083] Application Example 2

[0084] The leakage rate of the composite phase change materials prepared in Examples 1 to 3 was tested and compared with that of PEG.

[0085] Put the material into a 100℃ oven and observe the state at different times, such as Figure 7 As shown in (a), the mass loss of the material is recorded and the statistical result is Figure 7 The leakage rate is shown in (b). PEG has a serious leakage, with a leakage rate of 100%, while the composite phase change material with the support of the aerogel skeleton has the highest leakage rate of PEG@MC1, which is only about 5%, much lower than the leakage of PEG. The reason is that the MC three-dimensional framework has good hydrogen bonding, capillary force and interfacial tension, and the PEG polymer molecules are firmly embedded in the three-dimensional framework, while maintaining stability and not separating from each other, thus greatly reducing the leakage rate of the composite phase change material. At the same time, based on the high enthalpy efficiency of the composite phase change material with the support of the aerogel skeleton, the leakage of PEG is further suppressed.

[0086] Application Example 3

[0087] The composite phase change materials and pure PEG materials prepared in Examples 1 to 3 with a thickness of 1 mm were placed on a heating plate at 100° C. to observe the temperature changes of the materials and test the thermal conductivity of the materials. Figure 8The temperature curve in (a) and the thermal imaging real-time image in (b) show that the temperature of PEG and the composite phase change material can rise rapidly and stabilize after a period of time. Among them, due to the poor thermal conductivity and heat dissipation ability of PEG, the temperature cannot be quickly dissipated into the air, so the temperature accumulates inside it, which is manifested as a continuous increase in temperature until about 97°C, when the temperature tends to be constant after the heat absorption and heat dissipation of PEG tend to be equal; while the temperature of the composite phase change material is approximately stable at 68.4°C, 67.1°C and 66.4°C, respectively. With the support of the high thermal conductivity aerogel skeleton, the heat dissipation ability of the material is greatly improved, and the temperature of the heating plate diffuses into the air after passing through the composite phase change material, so that the temperature of the composite phase change material is maintained at a low level.

[0088] Figure 8 (c) further gives the thermal conductivity of each composite phase change material and PEG. With the support of the aerogel skeleton, the thermal conductivity of the composite phase change material has been greatly improved compared with PEG. The thermal conductivity of PEG@MC1 and PEG@MC2 has increased to 1.27W / m·K and 1.386W / m·K respectively, while the thermal conductivity of PEG@MC3 has reached an astonishing 1.446W / m·K, an increase of 286.7%, which is much higher than the 0.374W / m·K of pure PEG. The results show that the presence of the aerogel 3D skeleton can significantly improve the thermal conductivity of the composite phase change material.

[0089] Application Example 4

[0090] The present invention uses Agilent E5071C vector network analyzer to measure the electromagnetic shielding performance of the composite phase change material by a waveguide method.

[0091] Fig. 9 (a) provides the average electromagnetic shielding performance of the composite phase change material, (b) shows the maximum electromagnetic shielding performance of the composite phase change material, and (c) gives the electromagnetic shielding performance parameters of the composite phase change material, where A, R and T represent the absorption coefficient, reflection coefficient and transmission coefficient of the material, respectively, which are calculated by taking the average value of the X-band, SE T , SE R and SE A They are total shielding effect, reflection shielding effect and absorption shielding effect.

[0092] In the figure, the A value of the composite phase change material is higher than its R value, proving that absorption is the main EMI shielding mechanism. It can be seen that the electromagnetic shielding performance of the composite phase change material increases with the increase of its chitosan content. The average electromagnetic shielding of PEG@MC3 reaches 33.5dB, and the highest electromagnetic shielding performance reaches 40dB. Whether it is the average electromagnetic shielding or the highest electromagnetic shielding, the performance of PEG@MC3 far exceeds the conventional commercial electromagnetic shielding performance of 20dB.

[0093] Furthermore, (c) in the figure shows that as the electromagnetic shielding performance increases, R shows an increasing trend, A shows a decreasing trend, and the overall trend of T remains unchanged. (d) further gives the electromagnetic shielding mechanism of the composite phase change material. Most of the incident electromagnetic waves enter the internal structure of the composite phase change material at the first time. The internal three-dimensional framework reflects and scatters the incident electromagnetic waves multiple times, greatly extending its propagation path in the interconnected channels. Once disturbed by electromagnetic waves, the abundant carriers on the MXene sheets spontaneously migrate between the sheets and generate microcurrents, which attenuate the energy in the form of ohmic loss by converting energy into heat. Therefore, the prepared composite phase change material exhibits EMI shielding performance dominated by absorption. In addition, as a heterogeneous composite structure, a large number of interfaces are formed between PEG and MXene, which can capture the migrating free electrons, resulting in charge accumulation and triggering interface polarization loss. At the same time, Ti3C2T x The functional groups contained on the surface form a large number of dipole surfaces, and the direction of the dipole moment is deflected under the action of the induced electric field, resulting in dipole polarization loss. In summary, the EMI shielding mechanism of the composite phase change material is mainly ohmic loss, supplemented by interface polarization loss and dipole polarization loss.

[0094] At the same time, the electromagnetic shielding performance of the composite phase change material PEG@MC4 prepared in Comparative Example 3 was also tested, and the results showed that the material did not have an electromagnetic shielding effect.

[0095] Application Example 5

[0096] The photothermal conversion performance of the composite phase change material mainly depends on its ability to absorb light. The present invention enhances the photothermal conversion capability of the composite phase change material by introducing MXene with strong photothermal conversion capability.

[0097] The composite phase change materials prepared in Examples 1 to 3 were placed in a light-proof sealed box and heated at 130 mW / cm 2 Incandescent lamps are used to simulate sunlight, and thermocouples are installed on the surface of the composite phase change material to transmit the temperature changes on the material surface to the data collection module and output the data by the computer.

[0098] from Fig.10It was observed that under the irradiation of light, the temperature of the three composite phase change materials rose rapidly, and their heating curves can be roughly divided into three stages. The first stage is roughly from 0s to 600s. In this stage, the temperature rises rapidly in the early stage. In the later stage, as the temperature difference between the composite phase change material and the air becomes larger, the heat dissipation is further enhanced, and the heating rate of the composite phase change material slows down; the second stage is about 600s to 750s. In this stage, the temperature of the composite phase change material is basically unchanged. The reason is that the phase change occurs and absorbs the surrounding heat, so the temperature is basically unchanged; the third stage is roughly from 750s to 3200s. In this stage, the phase change is basically completed. The heat absorbed by the composite phase change material is mainly used to increase its own temperature, and the final temperature reaches about 85°C.

[0099] In summary, the composite phase change material prepared by the present invention has excellent electromagnetic shielding and good thermal conductivity, and also has a certain light-to-heat conversion function, which is beneficial for some equipment with long-term charge and discharge cycle requirements, such as the heat flow of batteries. It not only prevents local overheating and even thermal runaway problems, but the light-to-heat conversion function can also enable the entire battery or battery pack to convert energy under sunlight to store heat, which can be further utilized for the operation of equipment under extremely cold conditions, and can be placed in the equipment casing as a thermal management module.

[0100] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity and ultra-strong electromagnetic shielding composite phase change material based on MXene-based aerogel, which is made of MXene and chitosan as raw materials. The mixed solution is quickly and directionally frozen, and then vacuum dried to obtain an aerogel framework material, which is then carbonized at high temperature to obtain a MXene@CS three-dimensional framework material. The molten phase change material PEG is vacuum impregnated and adsorbed to obtain a shape-stable composite phase change material PEG@MC.

2. The composite phase change material according to claim 1, characterized in that The mixed solution is placed in a polytetrafluoroethylene mold with a copper plate at the bottom, and immersed in liquid nitrogen for rapid directional freezing.

3. The composite phase change material according to claim 1, characterized in that The mass ratio of MXene to chitosan is 1:1 to 2.

5.

4. The composite phase change material according to claim 1, characterized in that The MXene is a MXene suspension with a concentration of 7 to 10 mg / mL.

5. The composite phase change material according to claim 1, characterized in that The high temperature carbonization temperature is 380-400°C.

6. The composite phase change material according to claim 1, characterized in that The loading amount of PEG in the composite phase change material is greater than 98%.

7. The method for preparing the composite phase change material according to claim 1, comprising: 1) Prepare a MXene suspension with a concentration of 7-10 mg / mL; 2) preparing chitosan suspension and adjusting the pH value of the suspension to 5-6; 3) Mixing to obtain a mixed solution of MXene and chitosan, eliminating bubbles and placing it in a polytetrafluoroethylene mold on a copper bottom plate, rapidly freezing it in liquid nitrogen, and vacuum drying it in a freeze dryer to obtain an aerogel frame material; 4) Carbonizing the aerogel framework material at 380-400°C to obtain the MXene@CS three-dimensional framework material; 5) The MXene@CS three-dimensional framework material and excess PEG were placed in a vacuum oven at 80°C for vacuum impregnation treatment to obtain a PEG@MC composite phase change material.

8. The preparation method according to claim 7, characterized in that 1wt% acetic acid solution was used to adjust the pH value of the chitosan suspension.

9. The preparation method according to claim 7, characterized in that Carbonization time is 2 to 4 hours.

10. The preparation method according to claim 7, characterized in that The vacuum impregnation time is 8 to 10 hours.

Citation Information

Cited By

  • Electromagnetic shielding composite film and preparation method and application thereof

    CN120737421A